Extradigital glomangiomyoma of the forearm mimicking peripheral nerve sheath tumour and thrombosed varicose vein. Issue 4 (12th April 2021) - Li, Lily; Bardsley, Victoria; Grainger, Andrew; Johnston, Phillip
Abstract : Extradigital glomus tumour is uncommon, little-known outside of its subungual location, and may present without its classic triad of tenderness, cold sensitivity and paroxysmal pain. Imaging is non-specific and diagnosis is often delayed, sometimes for years, leading to unnecessary morbidity. Surgical excision is the treatment of choice, although technique depends on case specifics. Histological subtypes depend on the relative prominence of glomus cells, vascular structures and smooth muscle. The vast majority of glomus tumours are benign. We highlight the importance of considering extradigital glomus tumours when generating differential diagnoses of an atypical painful lesion in a variety of clinical specialties.